Effects of Giving Iodized Salt, Counseling of Iodine and Goitrogenic Sources of Food in Mothers Who Have Elementary School Children Against Urinary Iodine Excretion - I Ketut Swiryajaya; Iswari Pauzi (Humanistic Network for Science and Technology (HNST), 2019)
As a result of IDD is the occurrence of impaired child growth makes researchers interested in conducting research on